2003
DOI: 10.1161/01.str.0000053451.28410.98
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Risk of Ischemic Stroke

Abstract: Background and Purpose-Although prior studies have demonstrated that 25% to 35% of stroke patients have had a recent infection, the role of infection as a risk factor remains unclear. Our aim was to characterize the effect of infectious/inflammatory syndromes on stroke risk. Methods-Case-control and crossover analyses of 233 cases and 363 controls aged 21 to 89 years were performed. Cases were patients hospitalized with a first ischemic stroke at a Los Angeles, California, medical center. Controls were outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 32 publications
4
52
2
1
Order By: Relevance
“…Several observational clinical studies have reported associations between preceding common infections (mainly respiratory tract infections) and ischemic stroke (Grau et al 2010). The reported prevalence of preceding infection, and timing prior to index stroke varies considerably between these studies, and one study found no difference in the prevalence of recent infection between cases and controls (Paganini-Hill et al 2003). In the largest study, based on the UK General Practice Research…”
Section: The Immune System and Strokementioning
confidence: 99%
“…Several observational clinical studies have reported associations between preceding common infections (mainly respiratory tract infections) and ischemic stroke (Grau et al 2010). The reported prevalence of preceding infection, and timing prior to index stroke varies considerably between these studies, and one study found no difference in the prevalence of recent infection between cases and controls (Paganini-Hill et al 2003). In the largest study, based on the UK General Practice Research…”
Section: The Immune System and Strokementioning
confidence: 99%
“…29 Our data suggest that atrial fibrillation partially explains the infection-stroke association, consistent with previous reports of an association between acute infection and an increased risk of cardioembolic stroke. 12,30 Studies have also shown that acute infection is associated with stroke due to large-vessel atherothromboembolism. 12 Interestingly, cardioembolic strokes and largeartery infarcts are ischemic stroke types that are more common in whites compared with blacks.…”
mentioning
confidence: 99%
“…Furthermore, poststroke infections affect clinical outcome (164). Respiratory-and urinary tract infections are the most common types of infection preceding stroke after adjustment for age and conventional vascular risk factors (165,166).…”
Section: Systemic Inflammation and Infection: The Need For Appropriatmentioning
confidence: 99%